Antimicrobial treatment decision for non-purulent skin and soft tissue infections in the emergency department. Issue 3 (17th August 2016) - Yadav, Krishan; Gatien, Mathieu; Corrales-Medina, Vicente; Stiell, Ian
Abstract: Objectives: We surveyed Canadian emergency physicians to determine how skin and soft tissue infections (SSTIs) are managed and which risk factors were felt to be important in predicting failure with oral antibiotics. Methods: We performed an electronic survey of physician members of the Canadian Association of Emergency Physicians (CAEP) using the modified Dillman method. Results: The survey response rate was 36.9% ( n =391) amongst CAEP members. There was a lack of consensus regarding management of SSTIs. CAEP respondents identified 14 risk factors for predicting treatment failure with oral antibiotics, including hypotension, tachypnea, and patient reported severity of pain >8 of 10. Conclusions: The survey demonstrates significant variability regarding physician management of SSTIs, and we have identified several perceived risk factors for treatment failure with oral antibiotics that should be assessed in future studies. RÉSUMÉ: Objectifs: Une enquête a été menée parmi les médecins d'urgence au Canada afin de déterminer la prise en charge des infections non purulentes (INP) de la peau et des tissus mous, et de cerner les facteurs de risque jugés importants dans la prévisibilité de l'échec du traitement par les antibiotiques par voie orale. Méthode: Une enquête en ligne a été menée parmi les médecins membres de l'Association canadienne des médecins d'urgence (ACMU), selon une version modifiée de la méthode de Dillman. Résultats: Le taux de réponse parmi les membres de l'ACMU a atteint 36, 9 % (n=391), et un manque de consensus a été relevé quant à la prise en charge des INP de la peau et des tissus mous. Les répondants ont cerné 14 facteurs de risque de prévisibilité de l'échec du traitement par les antibiotiques par voie orale, notamment l'hypotension, la tachypnée et un degré d'intensité de la douleur déclaré par les patients, supérieur à 8/10. Conclusions: Les résultats de l'enquête démontrent que la prise en charge médicale des INP de la peau et des tissus mous varie passablement, et plusieurs facteurs de risque jugés importants dans la prévisibilité de l'échec du traitement par les antibiotiques par voie orale devraient faire l'objet d'études futures.